Seroprevalence of HBsAg among blood donarâs in Sher-E-Bangla Medical College, Barisal - Mahmood, G; Debnath, CR; Biswas, B (Bangladesh Liver Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Hepatitis B virus infection is a global health problem. About 350 to 400 million people are chronically infected with hepatitis B in the world. This is a retrospective study carried out in the department of transfusion medicine, Sher- E-Bangla Medical College Hospital, Barisal, during the period 1st January to 31st December 2007, among the blood donors who attended for blood donation. During this period 12,914 patients attended the department for transfusion. Among them 12,014 were male and 900 were female, age range was 18 to 60 years. Among them professional donors were 955, voluntary donors were 4494 and replacement donors were 7556 and HBsAg was positive in 0.42%, 0.87% and 1.11% respectively. Overall prevalence was 0.98%. The aim of this study was to determine the prevalence of HBsAg among blood donors at Sher-E-Bangla Medical College, Barisal. Blood samples were collected from 12914 healthy donors. All donors were pre-screened by a questionnaire provided by the institution and passed the physical examination conducted by the medical officer in charge. Blood donors data and results of HBsAg were analyzed using the blood bank's records. There was an overall prevalence of 0.98% of HBsAg(+) among all the tested blood donors. There was statistically significant difference between sexes. These results stress the importance of screening programs that must be implemented. doi: 10.3329/blj.v1i1.2624 Bangladesh Liver Journal Vol.1(1) 2009 p.38-40